Empowerment of Cultural Tourism in West Nias Using Social Media - Vera, Nawiroh; Dewi, Liza Dwi Ratna (RSF Conference Series: Business, Management and Social Sciences, 2021)
Tourism is a quarter that is growing to be the top mover of improvement inside the vicinity. Nature and cultural diversity are belongings owned by way of each region in Indonesia, that have the capacity to be advanced as traveler destinations. West Nias Regency is one area that has incredible ability to be advanced as a traveller destination, especially cultural tourism. The tourism industry these days can't be separated from the role of social media in book and promoting. numerous varieties of tourism, and tourism destinations in faraway regions can be recognized to the public through social media. One form of social media that has a photograph and video sharing characteristic is Instagram, so Instagram may be used as a medium in selling tourism through the posts of human beings inside the location. the motive of this research is how to empower cultural tourism in West Nias by using maximizing the usage of social media in this example is Instagram. The approach used is exploratory with a qualitative approach. The effects of the look at indicate that the promotion of cultural tourism in West Nias has now not been maximized, specially by way of utilizing social media.